The Effects of Accounting Standard Precision, Auditor Task Expertise, and Judgment Frameworks on Audit Firm Litigation Exposure - Grenier, Jonathan H.; Pomeroy, Bradley; Stern, Matthew T. (Contemporary Accounting Research, 2015)
Abstract Recent research suggests that adopting imprecise accounting standards elevates audit firm litigation exposure and could undermine auditor objectivity if audit firms respond by herding to industry norms. This paper reports the results of two experiments that demonstrate how audit firms can effectively mitigate the elevated litigation exposure without herding to industry norms by staffing engagements with recognized technical experts, using judgment frameworks and automated decision aids, and providing persuasive evidence of adherence to auditing standards. We find that judgment frameworks are particularly well‐suited for defending judgments under imprecise standards, and represent a cost‐effective alternative to using technical experts. However, our results also indicate that judgment frameworks may provide a safe harbor for relatively low‐quality judgments when those frameworks are used under precise standards. We discuss implications for audit firms, courts, and regulators that currently conduct or evaluate audits within and across jurisdictions where the precision of accounting standards varies considerably.